Multimodal treatment program in non-specific low back pain – A case series - Satria Nugraha, Made Hendra (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2022)
Non-specific low back pain (NSLBP) has a high prevalence among the population. NSLBP not only affects individuals but also has an impact on decreasing work productivity and ultimately affecting the economic sector. There are several multimodal that can be given to treat NSLBP. This case series is a preliminary study to determine the effectiveness of the combination of ultrasound therapy, stretching training, lumbar joint mobilization, and lumbopelvic stabilization training in NSLBP in improving pain and reducing back disability. The intervention was given three times in 1 week for four weeks (12 sessions) to 3 respondents. The effectiveness of therapy was assessed using a numeric rating scale (NRS) to measure pain reduction and the Indonesian version of the modified Oswestry disability index (MODI) to assess the decrease in lower back disability in NSLBP. Based on the results of the case series, there was a decrease in the average NRS value from 4.67 to 1.93 (with a difference in the average decrease of 2.74), and there was a decrease in the average MODI value from 32 to 13.67 (with a difference in the mean decrease of 18.33). The results of this case series provide information that the combination of UST, stretching exercise, joint mobilization, and lumbopelvic stabilization exercise is beneficial in reducing pain and disability in NSLBP. This case series is a preliminary study on the multimodal combination in the treatment of NSLBP. It is hoped that further experimental studies will be conducted to prove this combination's effectiveness in treating individuals with NSLBP.